SARTRE’S EXISTENTIALISM IN URSULA WILL JONES’S VUSI MAKUSI - SHOLIHIN, ACHMAD BUDI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: existentialism and essences, being for others, bad faith, Vusi Makusi. Vusi Makusi is a short story published in 2011, which has also become the runner up in Guardian newspaper’s short story competition. Makusi, as the main character, holds everything which he believes. He does everything based on his beliefs.The purpose of this research is to analyze Makusi as the main character in the short story creates his essences, which becomes an optimist person. “Optimist” here means he has a strong decision in doing everything. However, to others his decision is useless. Besides, this research also analyzes other characters. It is how others see Makusi with his strong belief.Sartre’s existentialism theory in his Being and Nothingness and in his Existentialism is Humanism become proper theory to describe why Makusi chooses himself to be someone who has a strong decision in choosing everything. It also becomes a proper theory to analyze others’s perspectives of Makusi. There are three concepts which are used to analyze Makusi and others. Those are Existentialism and Essence, Being for others and Bad faith.By analyzing and interpreting the data, it is known that the result is, Makusi has realized and even understood that no one can shape his essences except himself. It is also known that it is Makusi himself who decides himself becoming a person who has a strong decision in his own belief. Then, from his choice, it brings the risk of other’s judgments. Still he never bothers of it.